Ship Detection based on Synthetic Aperture Radar Technique - Agustan Agustan; Rubby Siddik Agustino (Indonesian Journal of Geospatial, 2014)
Abstract. The ability of radar signals to penetrate cloud is one advantage to be used in tropical regionto monitor objects on the surface from the space. Synthetic Aperture Radar (SAR) is onetechnique in radar remote sensing that can be utilized for marine applications such as surfacewaves monitoring, ocean current circulation detection, oil slick monitoring and shipdetection. In order to assess the ability of SAR technique for ship detection, we analyze SARdata acquired by full polarimetric and interferometric airborne SAR in L-band type-2 (Pi-SARL2) from Japan Aerospace Exploration Agency (JAXA). This research explains the strategy inSAR data processing for ship detection application in Lembeh Strait, North Sulawesi Sea. It isfound that long wavelength i.e. L-band is able to identify ships on the sea with incidence angleof radar beam greater then 50 degree gives the best signal clutter ratio between signal fromthe ship to sea clutter variation. The identification includes the size estimation and thelocation. Horizontal-Horizontal (HH) polarization can identify ships clearer in calm seacondition, whereas Horizontal-Vertical (HV) polarization is better in severe sea condition.However, it is difficult to estimate the speed of moving ships on the sea and the shipsmaterial. It is also found that by combining SAR data with VMS (Vessel Monitoring System)data it is possible to identify ships without VMS and useful for improving security issue inmarine sector. Keywords: SAR, ship detection, polarization, VMS